Hands-free radiographic canine hip distraction view with applied force monitoring - Santana A.; Alves-Pimenta S.; Martins J.; Cabral P.; Tomé I.; Colaço B.; Morais J.; Ferreira A.; Ginja M. (BMC Veterinary Research)
Abstract Background Canine Hip Dysplasia (CHD) is a prevalent orthopedic disorder in dogs, primarily characterized by hip joint laxity, which may lead to osteoarthritis and mobility impairments. Radiographic assessment, using the distraction view (DV) is considered the gold standard for evaluating hip laxity (HL). Veterinary professionals should take precautions to reduce exposure to ionizing radiation and its harmful effects. This study aims to compare the hip laxity of the DV obtained through manual restraining, with similar views using the positioning holder device PosUTAD, with an incorporated applied force monitoring system. Results In this prospective study, 59 dogs (118 joints) were x-rayed using the hip DV twice, one using manual restraint and another using the PosUTAD modified (Mod) holder device. The force to maintain the hips under stress ranged from 17.15 to 44.1 N, 21.0 ± 5.0 N. The mean distraction index (DI) in the pairs of radiographs was similar for manual 0.42 ± 0.11 and holder restraining 0.43 ± 0.12 (P > 0.05, Paired t-test), with the maximum DI difference of 0.12. The Bland–Altman analysis shows a good scatter of DI differences distribution with limits of the agreement between -0.10 and 0.10. The intraclass correlation coefficient was 0.90, with the inferior limit of the confidence interval of 0.86 (P < 0.05). Conclusions The PosUTAD Mod allows a reliable alternative technique to obtain the hip DV and avoids exposure of personnel to ionizing radiation. However, using the PosUTAD Mod device requires more specialized human resources, as the experience of an assistant to fix the PosUTAD Mod under adequate force is necessary for the success of the technique. It should also be added that it is a slightly more time-consuming technique, so it will only be an option when veterinary professionals’ exposure to ionizing radiation is not allowed or is valued.